Pengaruh Pendayagunaan Zakat Produktif terhadap Pemberdayaan Mustahiq di Lembaga Amil Zakat (LAZ) Musa’adatul Ummah Al Ma’soem - Jujun Jamaludin (Masoem University, 2019)
This research was carried out in Musa'adatul Ummah Al Ma'soem, an Amil Zakat Institution and a non-profit institution engaged in the collection of Zakat, Infaq and Alms. The results of ZIS fund collection are then rolled out to beneficiaries in the form of service and empowerment programs in the fields of education, economics, da'wah, and social humanity. The main problem of this research is the effect of productive zakat funds on mustahiq. The research design is quantitative and the analysis is statistical using simple regression. The results of this study indicate that productive zakat funds for the period 2016-2017 significantly affect mustahiq income. The amount of influence of the amount of funds (zakat) distributed to mustahiq income is 44.6%, while the remaining 55.4% of mustahiq income is influenced by other factors not examined.